2016
DOI: 10.7196/samj.2016.v106i5.10674
|View full text |Cite
|
Sign up to set email alerts
|

Emerging trends in non-communicable disease mortality in South Africa, 1997 - 2010

Abstract: NCDs contribute to premature mortality in SA, threatening socioeconomic development. While NCD mortality rates have decreased slightly, it is necessary to strengthen prevention and healthcare provision and monitor emerging trends in cause-specific mortality to inform these strategies if the target of 2% annual decline is to be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
52
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 38 publications
(23 reference statements)
7
52
1
11
Order By: Relevance
“…The World Health Organisation predicts that by 2030 most people will die from non-communicable diseases such as heart disease, stroke, cancer, diabetes, and chronic respiratory diseases 2 . Similarly in South Africa (SA), non-communicable diseases have been reported as one of the main causes of death 3 of which Nojilana, Bradshaw, Pillay-van Wyk et al 3 found that, stroke was the number one cause 3 . The prevalence of stroke for people from 15 years and older, is 3 for every 1 000 in South Africa 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organisation predicts that by 2030 most people will die from non-communicable diseases such as heart disease, stroke, cancer, diabetes, and chronic respiratory diseases 2 . Similarly in South Africa (SA), non-communicable diseases have been reported as one of the main causes of death 3 of which Nojilana, Bradshaw, Pillay-van Wyk et al 3 found that, stroke was the number one cause 3 . The prevalence of stroke for people from 15 years and older, is 3 for every 1 000 in South Africa 4 .…”
Section: Introductionmentioning
confidence: 99%
“…However, different trends in cause-specific non-communicable diseases were observed; for example, tobacco-related mortality has declined, while deaths from diabetes and renal disease have increased. [1,7] Furthermore, injury deaths have declined since the late 1990s, with a 52% decrease in agestandardised death rates between 1997 and 2012. [1] Interestingly, the top ten single causes of death have not changed over the 16-year period, and include causes from all four broad cause groupings, i.e.…”
Section: Guest Editorialmentioning
confidence: 99%
“…Our study shows that NCDs are already among the top causes of death in SA [3] By 2010, NCDs accounted for 39% of total deaths in the country. More than a third (36%) of these deaths occurred before the age of 60 years.…”
mentioning
confidence: 99%
“…The substantial decrease in mortality from oesophageal cancer may be due to changing socioeconomic status, urbanisation and resultant dietary changes, including shifts from consuming home-grown to commercial maize. [7] Persistent burden from non-communicable diseases in South Africa needs strong action [3] (IHD = ischaemic heart disease; COPD = chronic obstructive pulmonary disease.) Cardiovascular diseases were the leading category of NCDs.…”
mentioning
confidence: 99%